Recursive Method to Extract Rectangular Objects from Scans - Herley, Cormac (Institute of Electrical and Electronics Engineers, Inc., 2003)
In scanning photographs, receipts or other small objects users will often scan many at a time. It would be convenient to automatically detect that the scanned image consists of many small objects rather than a single large one, and segment appropriately. We present a simple, efficient and robust way of doing this.